Flexible aramid nanofiber conductive film and preparation method and application thereof

Prepare flexible aramal nanofiber conductive membrane through vacuum -assisted filtration and chemical nickel plating treatment, solving the problem of poor performance of polymer base flexible conductive film at high temperature and metal conductive fillers. Electromagnetic shielding performance.

CN119352288AActive Publication Date: 2025-01-24SICHUAN UNIV

Patent Information

Application Number
CN202411488761.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-24
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

In the prior art, polymer-based flexible conductive films have poor performance at high temperatures, and metal conductive fillers are prone to oxidation, resulting in a degradation of electromagnetic shielding performance.

Method used

The modified aramid nanofiber membrane is prepared through vacuum-assisted filtration, and electroless nickel plating is performed under an external magnetic field, combined with polydimethylsiloxane encapsulating liquid dip coating to form a flexible aramid nanofiber conductive membrane.

Benefits of technology

Realize efficient conductivity and excellent electromagnetic shielding performance, while maintaining the flexibility and corrosion resistance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119352288A_ABST
    Figure CN119352288A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electromagnetic shielding materials and conductive polymer-based composite materials, and particularly relates to a flexible aramid nanofiber conductive film and a preparation method and application thereof. The preparation method comprises the following steps: firstly, preparing an aramid nanofiber membrane through vacuum-assisted filtration, and then immersing the aramid nanofiber membrane into a nickel ion-containing solution for ultrasonic pretreatment and activation treatment by a sodium borohydride solution to obtain a modified aramid nanofiber membrane; and mixing with a chemical nickel plating solution under an external magnetic field, drying, and dip-coating with a polydimethylsiloxane packaging solution to obtain the flexible aramid nanofiber membrane. The finally obtained flexible aramid nanofiber conductive film has excellent flexibility, heat resistance and corrosion resistance. The method is easy to operate, economical and environmentally friendly, the material has excellent electromagnetic shielding performance due to the porous layered structure of the formed nanofiber membrane and the nickel coating on the surface, and the problem of mutual interference between electronic elements can be solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electromagnetic shielding materials and conductive polymer-based composite materials, and specifically relates to a flexible aramid nanofiber conductive film and a preparation method and application thereof. Background Art

[0002] With the full coverage of the fifth generation of communications (5G), electromagnetic waves bring convenience to human life but also come with huge potential hazards. Not only does it affect people's physical health, it has also become a factor affecting the performance of aircraft, satellites and many other important fields of equipment, causing great trouble to people's lives and work. In the past, metals with high conductivity were usually selected as shielding materials, but the disadvantages of metal materials such as high rigidity and difficulty in bending limited their application. In addition, although metal materials still have high utilization value, many methods based on electrochemical metal plating often have complicated steps and high energy consumption. Therefore, it is becoming increasingly important to design a flexible material with high electromagnetic shielding performance and a low-cost method, and future demand is also continuing to grow.

[0003] At present, conductive polymer-based composite materials can largely solve the problem of high material rigidity, and they have the advantages of low cost, low density, wide application range and strong designability. Different polymers can be selected as matrix materials according to actual application requirements to obtain conductive composite materials with good flexibility. Commonly used polymer matrix materials include polyetheretherketone, polyester, polyimide, polyolefin, polylactic acid, epoxy resin, silicone rubber, etc. Polymer-based flexible conductive films mainly use flexible polymer materials as the matrix, and metal-based fillers (such as metal particles, metal nanowires, etc.), carbon-based fillers, conductive polymer fillers and other conductive fillers are coated on the surface of the matrix or embedded in the inside to form a conductive path, thereby achieving controllable conductivity. The preparation methods mainly include blending, chemical plating, surface coating, spraying, electroplating, vapor deposition, sol-gel, microporous foaming and isolation structure. However, some polymer matrices themselves have poor heat resistance, and it is impossible to ensure that they still have good comprehensive performance at high working temperatures, and it is difficult to meet the application requirements of flexible conductive films. In addition, metals such as copper and silver are easily oxidized when exposed to the environment, which limits the application of conductive fillers. The patent with application number CN202410297420.4 discloses a method for coating carbon nanotubes on the surface of polyurethane / non-woven fabric materials. The polyurethane / non-woven fabric material is immersed in a conductive impregnation liquid by a dip coating method, and the conductive layer is tightly combined with the material surface by physical action. The polyurethane material used in this method has poor heat resistance, and the use temperature generally does not exceed 150°C. Moreover, it is easy to fall off during use through dip coating, which will lead to poor conductivity and electromagnetic shielding performance of the final coating. The patent with application number CN201610899123.2 discloses a method for copper plating on the surface of polytetrafluoroethylene materials, using low-temperature plasma treatment. The conductive filler metal copper used in this method is easily oxidized when exposed to the environment, and has poor corrosion resistance, which will eventually lead to a decrease in shielding performance and conductivity in some corrosive fields. Therefore, a polymer-based flexible conductive film with good heat resistance and good mechanical properties is urgently needed in this field. Summary of the invention

[0004] Based on the above problems, the purpose of this application is to overcome the defects of the prior art and provide a flexible aramid nanofiber conductive film and a preparation method thereof to improve the electromagnetic shielding performance of the material.

[0005] To this end, the first technical solution of the present application discloses a method for preparing a flexible aramid nanofiber conductive film, comprising the following steps:

[0006] Preparation of modified aramid nanofiber membrane: vacuum-assisted filtration of aramid nanofiber dispersion to obtain flexible aramid nanofiber membrane, then immersing in nickel ion-containing solution-1 for ultrasonic treatment to obtain pretreated flexible aramid nanofiber membrane, and then immersing in sodium borohydride solution for activation to obtain modified flexible aramid nanofiber membrane;

[0007] Prepare a chemical nickel plating solution: add sodium citrate and sodium hypophosphite to the nickel ion-containing solution-2 and adjust the pH to 10 to obtain;

[0008] Preparation of flexible aramid nanofiber conductive film: Under an external magnetic field, the modified flexible aramid nanofiber membrane is immersed in a chemical nickel plating solution and then dried, and then dip-coated with a polydimethylsiloxane encapsulation solution and then dried to obtain a flexible aramid nanofiber conductive film.

[0009] Furthermore, the aramid nanofibers are dispersed in the aramid nanofiber dispersion, and the aramid nanofibers are one or more of para-aramid yarn fibers, para-aramid staple fibers, para-aramid fabric fibers, para-aramid fibrils, para-aramid pulp, meta-aramid staple fibers, meta-aramid fibrils, and meta-aramid filaments.

[0010] Furthermore, the vacuum-assisted filtration pressure is 0.4-0.8 MPa.

[0011] Furthermore, the ultrasonic treatment power is 40-240w.

[0012] Furthermore, the mass percentage concentration of the nanofiber membrane is 5wt% to 11wt% of the total mass of the chemical plating solution and the nanofibers;

[0013] Furthermore, the mass percentage concentration of the nanofiber membrane is 5wt% to 11wt% of the total mass of the chemical nickel plating solution and the aramid nanofibers.

[0014] Further, in terms of mass percentage concentration, the nickel ion solution-1 contains Ni 2+ 1wt%-6wt%, containing nickel ion solution-2 Ni 2+ 6wt%-18wt%.

[0015] Furthermore, the strength of the external magnetic field is 100-400 mT.

[0016] And, a flexible aramid nanofiber conductive film prepared according to the above preparation method.

[0017] The second technical solution of the present application discloses the application of the above-mentioned flexible aramid nanofiber conductive film in the preparation of shielding materials; and

[0018] A shielding material comprises the above-mentioned flexible aramid nanofiber conductive film.

[0019] The present invention has the following beneficial effects:

[0020] The present invention first prepares an aramid nanofiber membrane by vacuum-assisted filtration, then immerses it in a nickel ion solution for ultrasonic pretreatment and sodium borohydride solution activation treatment to obtain a modified aramid nanofiber membrane, and then mixes it with a chemical nickel plating solution under an external magnetic field, dries it, and dip-coats it with a polydimethylsiloxane encapsulation solution to obtain a flexible aramid nanofiber membrane. In this process, the ultrasonic treatment allows the micro-jets generated in the ultrasonic bath to form new active points on the surface of the nanofiber membrane, which promotes the oxidation of hydroxyl groups on the surface of the fiber membrane to form carboxyl groups. The increase in the number of polar functional groups is beneficial to the wettability of the nanofiber, that is, it helps the carboxyl groups on the surface of the fiber membrane to react with Ni. 2+ contact; using conductive and magnetic nickel nanoparticles as conductive fillers, preparing a chemical nickel plating solution, with the help of external magnetic field induction, the nickel nanoparticles are oriented and distributed to form an ideal conductive path, so that the aramid nanofiber conductive film has efficient conductivity; then using polydimethylsiloxane encapsulation liquid dip coating, so that the coating and the substrate have good bonding force, prevent the conductive layer from falling off while maintaining the flexibility of the nanofiber membrane, making it super hydrophobic, and can further enhance the corrosion resistance of the conductive film; finally, the obtained flexible aramid nanofiber conductive film has excellent flexibility, heat resistance, and corrosion resistance. The method is easy to operate, economical and environmentally friendly, and the porous layered structure of the formed nanofiber membrane and the nickel coating on the surface make the material have excellent electromagnetic shielding performance, which can solve the problem of mutual interference between electronic components. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a SEM image of the aramid nanofiber conductive composite film of Example 1 of the present invention.

[0022] Figure 2 This is the XRD spectrum of the aramid nanofiber membrane and the flexible conductive nanofiber membrane in Example 1 of the present invention.

[0023] Figure 3 The changes in the electrical conductivity and shielding performance of the flexible conductive nanofiber membrane of Example 1 of the present invention when subjected to different magnetic field intensities.

[0024] Figure 4 This is the change in the microscopic morphology and sheet resistance of the flexible conductive nanofiber membrane in Example 1 of the present invention under different environments.

[0025] Figure 5 This is the TGA graph of the aramid nanofiber membrane and the flexible conductive nanofiber membrane in Example 1 of the present invention. DETAILED DESCRIPTION

[0026] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] Unless otherwise specifically stated, the relative arrangement, numerical expressions and numerical values ​​of the parts and steps set forth in these embodiments do not limit the scope of the present application. At the same time, it should be understood that, for ease of description, the sizes of the various parts shown in the accompanying drawings are not drawn according to the actual proportional relationship. The technology, method and equipment known to those of ordinary skill in the relevant field may not be discussed in detail, but in appropriate cases, the technology, method and equipment should be considered as a part of the authorization specification. In all examples shown and discussed here, any specific value should be interpreted as being merely exemplary, rather than as a limitation. Therefore, other examples of exemplary embodiments may have different values. It should be noted that similar reference numerals and letters represent similar items in the following drawings, so that once a certain item is defined in an accompanying drawing, it does not need to be further discussed in subsequent drawings.

[0028] The first embodiment of the present application discloses a method for preparing a flexible aramid nanofiber conductive film, comprising the following steps:

[0029] Preparation of modified aramid nanofiber membrane: vacuum-assisted filtration of aramid nanofiber dispersion to obtain flexible aramid nanofiber membrane, then immersing in nickel ion-containing solution-1 for ultrasonic treatment to obtain pretreated flexible aramid nanofiber membrane, and then immersing in sodium borohydride solution for activation to obtain modified flexible aramid nanofiber membrane;

[0030] Prepare a chemical nickel plating solution: add sodium citrate and sodium hypophosphite to the nickel ion-containing solution-2 and adjust the pH to 10 to obtain;

[0031] Preparation of flexible aramid nanofiber conductive film: Under an external magnetic field, the modified flexible aramid nanofiber membrane is immersed in a chemical nickel plating solution and then dried, and then dip-coated with a polydimethylsiloxane encapsulation solution and then dried to obtain a flexible aramid nanofiber conductive film.

[0032] In this embodiment, the aramid nanofiber dispersion is a mixture in which aramid fibers are dispersed, and its preferred preparation method is specifically as follows: substance A and substance B are mixed at a ratio of (0.3-3.0) g:20 mL, substance A is potassium hydroxide, potassium tert-butoxide or sodium hydroxide, and substance B is one or more of deionized water, ethanol and methanol to obtain solution A; wherein solution A is mixed with one or more of dimethyl sulfoxide and N,N-dimethylacetamide at a ratio of 20 mL:500 mL to obtain a mixed system B; wherein aramid fibers are added to the mixed system B at a ratio of 2 g:520 mL, and stirred continuously at 20-80° C. to obtain an aramid nanofiber dispersion. wherein the continuous stirring temperature is 20-80° C., the stirring speed is 800-1200 r / min, and the stirring time is 1-7 days.

[0033] In a further embodiment, the aramid fiber in the preparation of the aramid fiber nano-dispersion is the full name of poly(p-phenylene terephthalamide), which is a synthetic fiber; the fibers preferably used in this application are any one or more of para-aramid yarn fibers, para-aramid staple fibers, para-aramid fabric fibers, para-aramid fibrils or para-aramid pulp, meta-aramid staple fibers, meta-aramid fibrils, and meta-aramid filaments.

[0034] It can be understood that in the vacuum-assisted filtration process, in order to improve the filtration efficiency, the present application preferably adds the aramid fiber nano-dispersion into deionized water for filtration, and the filtration pressure is preferably 0.4-0.8Mpa, and the filtered components are further dried at a drying temperature of 40-80°C.

[0035] In a further embodiment, the flexible aramid nanofiber membrane obtained by vacuum assisted filtration drying is immersed in a nickel ion solution for ultrasonic treatment. The ultrasonic treatment causes the microjets generated in the ultrasonic bath to form new active points on the surface of the nanofiber flexible film, promoting the oxidation of hydroxyl groups on the surface of the fiber membrane to form carboxyl groups, thereby increasing the oxygen-containing polar functional groups on the surface of the fiber membrane, which helps to improve the wettability of the fiber membrane surface, improve the surface activity of the fiber membrane, and help the carboxyl groups on the surface of the fiber membrane to react with Ni 2+ Contact, so that it undergoes a coordination reaction to form a coordination bond -COO-Ni, thereby modifying and modifying the metal ions, stabilizing the metal ions on the ligand molecules, and improving the binding force between the fiber membrane and the metal ions. In order to achieve the above purpose, the ultrasonic treatment power is 40-240w.

[0036] In this embodiment, the nickel ion solution-1 is obtained by dissolving a nickel salt. The preferred nickel salt in this application is nickel chloride hexahydrate, specifically, nickel chloride hexahydrate is added to deionized water and mixed until it is completely dissolved. When nickel chloride hexahydrate is used as the nickel salt, the applicant determines through gradient experiments that the concentration of the nickel chloride solution is 2-10 g / L, preferably 7 g / L. At this time, in terms of mass percentage concentration, Ni 2+ Concentration 1wt%-6wt%

[0037] In a further embodiment, the pre-treated flexible aramid nanofiber membrane after ultrasonic treatment is immersed in a sodium borohydride solution for activation, the purpose of which is to better reduce the metal nickel ions on the surface of the fiber membrane in the subsequent chemical nickel plating process. Compared with the palladium activation process commonly used in the prior art, the present application uses sodium borohydride to activate the fiber membrane, which can significantly save and reduce costs.

[0038] In this embodiment, the preparation method of the chemical nickel plating solution is to add sodium citrate and sodium hypophosphite to the nickel ion-containing solution-2 and then adjust the pH to alkaline.

[0039] The preparation method of the nickel ion solution-2 is consistent with that of the nickel ion solution-1, wherein, in terms of mass percentage concentration, Ni 2+ The content is preferably 6wt%-18wt% of the nickel ion solution-2.

[0040] In a further embodiment, the purpose of adding sodium citrate and sodium hypophosphite is to improve the quality of the coating and ensure the stability of the electroplating process. Sodium citrate can form a stable complex with nickel ions, which can prevent nickel ions from precipitating or being reduced in the electrolyte, thereby helping nickel ions to stably exist in the electrolyte. At the same time, sodium citrate can promote the formation of deposits and enhance the adhesion between the deposits and the substrate. In addition, the chemical plating system containing sodium hypophosphite is environmentally friendly. In order to ensure the high conductivity of the resulting coating and form a coating with a low phosphorus content, it is selected to perform chemical nickel plating in an alkaline environment. Therefore, the pH range can be 8 to 14. The present application is preferably pH = 10, and for this reason, the addition ratio of nickel ion solution to sodium citrate and sodium hypophosphite is preferably 1.9:1:1.7.

[0041] In this embodiment, the strength of the external magnetic field for preparing the flexible aramid nanofiber conductive film is 100-400mT; under this external magnetic field, the nickel nanoparticles in the nickel ion solution can be oriented and distributed to form an ideal conductive path, so that the aramid nanofiber conductive film has efficient conductivity.

[0042] It should be noted that in the prior art, when selecting nickel as a conductive filler, metal nickel is generally directly blended with a matrix material. However, this composite method will lead to uneven dispersion of nickel nanoparticles. The nickel nanoparticles and the matrix material are only combined by physical forces, which will also cause problems with shielding performance and stability; or the traditional palladium activation process is used to chemically deposit nickel, which will lead to high costs and environmental pollution. The present application induces nickel ions into an oriented conductive path through an external magnetic field, which not only makes the nickel nanoparticles evenly dispersed, but also reduces costs.

[0043] It can be understood that after the modified flexible nanofiber membrane is immersed in a chemical nickel plating solution and treated with an external magnetic field, the surface is a wet fiber membrane; therefore, in a further embodiment, it is necessary to place the wet modified aramid nanofiber membrane wrapped by nickel nano-ions on a carrier for drying, and the carrier is preferably any one of a polytetrafluoroethylene plate, a glass substrate, a stainless steel plate or a cellulose acetate film, and the drying temperature is 40-80°C.

[0044] In this embodiment, the membrane obtained after drying is dip-coated with polydimethylsiloxane encapsulation liquid and then dried to obtain a flexible aramid nanofiber conductive membrane.

[0045] Among them, the use of polydimethylsiloxane encapsulation liquid dip coating can make the coating have good bonding force with the substrate, prevent the conductive layer from falling off while maintaining the flexibility of the nanofiber membrane, making it super hydrophobic, and can further enhance the corrosion resistance of the conductive film. The polydimethylsiloxane encapsulation liquid is prepared by the following method: the polydimethylsiloxane base liquid and the solvent are mixed in a ratio of 1:1 to 1:10. The solvent is one or more of xylene, n-hexane and n-decane.

[0046] Thus, the obtained flexible aramid nanofiber conductive film has excellent flexibility, heat resistance and corrosion resistance. The method is easy to operate, economical and environmentally friendly. The porous layered structure of the formed nanofiber membrane and the nickel coating on the surface give the material excellent electromagnetic shielding performance, which can solve the problem of mutual interference between electronic components.

[0047] The technical effects of the present invention will be more clearly described below in conjunction with the accompanying drawings and specific embodiments.

[0048] Example 1 Preparation of flexible aramid nanofiber conductive film

[0049] S1. Preparation of aramid nanofiber dispersion: Potassium tert-butoxide and methanol are mixed to obtain solution A for use, and then para-aramid fabric fiber, solution A, and dimethyl sulfoxide are mixed in a ratio of 2 g:20 mL:500 mL. After stirring at 900 r / min at 70°C for 1 day, deionized water is added to obtain a dark red aramid nanofiber dispersion with a concentration of 1.2 mg / mL.

[0050] S2. Prepare a modified flexible aramid nanofiber membrane: add the aramid nanofiber dispersion to deionized water; use a sand core funnel and a 0.45 μm microporous filter membrane to vacuum-assisted filter the prepared nanofiber dispersion, the vacuum degree of the vacuum-assisted filtration is 0.6 MPa, and dry at 80°C to obtain a flexible aramid nanofiber membrane. Preferably, 5wt% is used as the mass percentage concentration of the nanofiber membrane: 5.6g of the obtained flexible aramid nanofiber membrane is immersed in a nickel chloride solution with a concentration of 7g / L for ultrasonic treatment, washed with deionized water, and dried at 80°C to obtain a pretreated flexible aramid nanofiber membrane; the pretreated flexible aramid nanofiber membrane is immersed in a sodium borohydride solution for activation, and the modified flexible aramid nanofiber membrane is obtained after washing and drying for standby use.

[0051] S3. Preparation of flexible aramid nanofiber conductive membrane: Weigh 2g nickel chloride and add 100mL deionized water to mix until completely dissolved, then add 2g sodium citrate and sodium hypophosphite in sequence to form a Ni-containing 2+ The green transparent solution was then adjusted to pH 10.0 with a 20wt% sodium hydroxide solution, and then an external magnetic field with a strength of 120mT was introduced to place the modified flexible aramid nanofiber membrane into a chemical nickel plating solution. The wet nickel nanoparticle-wrapped aramid nanofiber membrane was placed on a polytetrafluoroethylene plate for drying, and finally the prepared polydimethylsiloxane solution was dip-coated thereon, and dried at 80°C to obtain a flexible aramid nanofiber conductive membrane.

[0052] In addition, referring to the preparation method of Example 1, the applied electric field strength of step S3 was changed to 214mT and 340mT to obtain a flexible aramid nanofiber conductive membrane, which were respectively recorded as Example 2 (214mT) and Example 3 (340mT).

[0053] Comparative Example 1 Preparation of Flexible Aramid Nanofiber Membrane

[0054] The preparation method is the same as S1-S2 in Example 1: the aramid nanofiber dispersion is subjected to vacuum-assisted filtration and then dried to obtain the obtained dispersion.

[0055] Comparative Example 2 Preparation of Flexible Aramid Nanofiber Conductive Film

[0056] The preparation method is the same as that of Example 1, except that in step S3 of Comparative Example 2, no external magnetic field treatment is performed.

[0057] Experimental Example 1 Characterization of the structure of flexible aramid nanofiber conductive film

[0058] The flexible aramid nanofiber conductive membranes prepared in Example 1 (Ni@NAF) and Comparative Example 1 (NAF) were characterized. Figure 1 This is a SEM image of the flexible aramid nanofiber conductive membrane of Example 1. It can be seen that nickel nanoparticles are formed on the surface of the nanofiber membrane, and a continuous nickel coating is formed to fill the pore structure of the original nanofiber membrane. Figure 2 The XRD spectra of the flexible aramid nanofiber membrane of Example 1 and the flexible aramid nanofiber conductive membrane of Example 1 are shown in Figure 1. Compared with the comparative example 1, the peaks of the XRD spectrum of the conductive nanofiber membrane of Example 1 at 44.8°, 51.3° and 77.2° belong to the characteristic peaks of metallic nickel, which confirms that Ni 2+ The successful reduction of shows that the flexible aramid nanofiber conductive film has been successfully prepared.

[0059] Test Example 2 Electromagnetic Shielding Test

[0060] The flexible aramid nanofiber conductive film prepared in Example 1 was used as an electromagnetic shielding material to test its conductivity and shielding performance under different magnetic field intensities. The specific steps are as follows:

[0061] The flexible aramid nanofiber conductive film is cut into discs with a diameter of 12 mm. The conductivity of the conductive performance is tested using a four-probe, and the shielding performance is tested using a vector network analyzer with a measurement frequency range of 8.2-12.4 GHz. When the flexible aramid nanofiber conductive film is used as a shielding material, its shielding mechanism is that the reflection attenuation of electromagnetic waves first occurs on the surface of the material; secondly, the electromagnetic waves that penetrate the surface are absorbed inside the material and further attenuated; finally, multiple reflections inside the material will also cause electromagnetic waves to attenuate. The electromagnetic shielding effectiveness (EMI SE) is calculated by the following formula: SE T =SE A +SE R+ SE M , where SE T is the total electromagnetic shielding efficiency, SE A is the efficiency of electromagnetic wave absorption loss, SE R Indicates the efficiency of electromagnetic wave reflection loss, SE M It is the efficiency of multiple reflection loss of electromagnetic waves. Figure 3It is a graph showing the changes in conductivity and shielding performance under different magnetic field strengths, wherein N-7 represents nickel chloride in a chemical nickel plating solution, the nickel chloride concentration used is 7 g / L, and no external magnetic field treatment is performed (Comparative Example 2), NM7-1, NM7-2, and NM7-3 represent nickel chloride in a chemical nickel plating solution, the nickel chloride concentration used is 7 g / L, and the external magnetic field is 120 mT (Example 1), 214 mT (Example 2), and 340 mT (Example 3), respectively. Figure 3 -(a) The results show that N7 has a relatively low conductivity, and at the same concentration, the flexible aramid nanofiber conductive membrane prepared in the presence of a magnetic field exhibits higher conductivity than the conductive fiber membrane prepared without the aid of magnetic field induction. For example, the conductivity of NM7-M3 is 7 times that of N7. Figure (b) shows that the change trend of EMI SE is consistent with the conductivity, and the EMI SE of the conductive nanofiber membrane is significantly improved after magnetic field induction. For example, the EMI SE of NM7-M3 is 36dB higher than that of N7. This shows that the conductive nanofiber membrane has excellent conductivity and shielding properties, and the magnetic field force enables the nickel nanoparticles to be oriented and arranged, thereby promoting the formation of an ordered structure conductive network.

[0062] Test Example 3 Stability and Corrosion Resistance Test

[0063] The flexible aramid nanofiber conductive membranes of Example 1 (Ni@NAF) and Comparative Example 1 (NAF) were immersed in 10wt% HCl, 10wt% NaOH and 5wt% NaCl solutions for 48 hours for corrosion resistance tests to evaluate the corrosion resistance of the nickel coating. Figure 4 This is a graph showing the changes in microscopic morphology and sheet resistance after the corrosion resistance test of Example 1. It can be observed that in an acidic environment, the nickel coating on the surface is corroded to a certain extent, a "worm-like" structure appears, and the sheet resistance increases significantly; while in an alkaline and saline environment, the overall morphology and sheet resistance are almost unaffected. This shows that the prepared conductive nanofiber membrane has relatively weak resistance to acidic environments, but has good stability in alkaline and saline environments. Figure 5 The TGA curves of the flexible aramid nanofiber membrane of comparative example 1 and the flexible aramid nanofiber conductive membrane of example 1 show that the decomposition temperatures of the flexible aramid nanofiber membrane and the flexible nanofiber conductive membrane are both above 500°C, indicating that the flexible conductive nanofiber membrane has good thermal stability. After chemical nickel plating, the initial decomposition temperature and the complete decomposition temperature of the fiber membrane are both increased.

[0064] The above embodiments are only used to illustrate the technical solutions of the present invention, but the protection scope of the present invention is not limited thereto. The embodiments of the present invention and the features in the embodiments can be arbitrarily combined with each other without conflict. Any technician familiar with the technical field can easily think of changes or replacements within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing a flexible aramid nanofiber conductive film, characterized in that: The steps include: Preparation of modified aramid nanofiber membrane: vacuum-assisted filtration of aramid nanofiber dispersion to obtain flexible aramid nanofiber membrane, then immersing in nickel ion-containing solution-1 for ultrasonic treatment to obtain pretreated flexible aramid nanofiber membrane, and then immersing in sodium borohydride solution for activation to obtain modified flexible aramid nanofiber membrane; Preparation of chemical nickel plating solution: adding sodium citrate and sodium hypophosphite to nickel ion-containing solution-2 and adjusting the pH to alkaline; Preparation of flexible aramid nanofiber conductive film: Under an external magnetic field, the modified flexible aramid nanofiber membrane is immersed in a chemical nickel plating solution and then dried, and then dip-coated with a polydimethylsiloxane encapsulation solution and then dried to obtain a flexible aramid nanofiber conductive film.

2. The preparation method according to claim 1, characterized in that: The aramid nanofibers are dispersed in the aramid nanofiber dispersion, wherein the aramid nanofibers are one or more of para-aramid yarn fibers, para-aramid staple fibers, para-aramid fabric fibers, para-aramid fibrils, para-aramid pulp, meta-aramid staple fibers, meta-aramid fibrils, and meta-aramid filaments.

3. The preparation method according to claim 1, characterized in that: The vacuum-assisted filtration pressure is 0.4-0.8 MPa.

4. The preparation method according to claim 1, characterized in that: The ultrasonic treatment power is 40-240w.

5. The preparation method according to claim 1, characterized in that: The mass percentage concentration of the nanofiber membrane is 5wt% to 11wt% of the total mass of the chemical nickel plating solution and the aramid nanofiber.

6. The preparation method according to claim 1, characterized in that: In terms of mass percentage concentration, the nickel ion solution contains Ni 2+ 1wt%-6wt%, containing nickel ion solution-2 Ni 2+ 6wt%-18wt%.

7. The preparation method according to claim 1, characterized in that: In the preparation of the chemical nickel plating solution, the addition ratio of the nickel ion solution, sodium citrate and sodium hypophosphite is: 1.9:1:1.7。 8. The preparation method according to claim 1, characterized in that: The strength of the external magnetic field is 100-400 mT.

9. A flexible aramid nanofiber conductive film prepared according to any one of the preparation methods described in claims 1-7.

10. Use of the flexible aramid nanofiber conductive film according to claim 8 in the preparation of shielding materials.

Citation Information

Patent Citations

  • Surface palladium-free chemical copper plating method of polytetrafluoroethylene materials

    CN107955939A

  • Polyurethane / non-woven electromagnetic shielding material and preparation method thereof

    CN118065128A

  • Method for preparing aramid fiber nickel / copper plating double-plating-layer composite conductive fibers

    CN105256291A

  • Polyaniline / aramid nanofiber conductive composite film and preparation method thereof

    CN110628215A

  • CNF-stabilized styrene-acrylic emulsion as well as preparation method and application thereof

    CN112745451A

Cited By

  • Electromagnetic shielding flexible composite film mainly based on absorption and preparation method of electromagnetic shielding flexible composite film

    CN120957402A